Intended and unintended consequences of abortion law reform: perspectives of abortion experts in Victoria, Australia. Issue 1 (2nd December 2016) - Keogh, L A; Newton, D; Bayly, C; McNamee, K; Hardiman, A; Webster, A; Bismark, M
Abstract : Introduction: In Victoria, Australia, abortion was decriminalised in October 2008, bringing the law in line with clinical practice and community attitudes. We describe how experts in abortion service provision perceived the intent and subsequent impact of the 2008 Victorian abortion law reform. Methods: Experts in abortion provision in Victoria were recruited for a qualitative semi-structured interview about the 2008 law reform and its perceived impact, until saturation was reached. Nineteen experts from a range of health care settings and geographic locations were interviewed in 2014/2015. Thematic analysis was conducted to summarise participants' views. Results: Abortion law reform, while a positive event, was perceived to have changed little about the provision of abortion. The views of participants can be categorised into: (1) goals that law reform was intended to address and that have been achieved; (2) intent or hopes of law reform that have not been achieved; (3) unintended consequences; (4) coincidences; and (5) unfinished business. All agreed that law reform had repositioned abortion as a health rather than legal issue, had shifted the power in decision making from doctors to women, and had increased clarity and safety for doctors. However, all described outstanding concerns; limited public provision of surgical abortion; reduced access to abortion after 20 weeks; ongoing stigma; lack of a state-wide strategy for equitable abortion provision; and an unsustainable workforce. Conclusion: Law reform, while positive, has failed to address a number of significant issues in abortion service provision, and may have even resulted in a 'lull' in action.